ANALISIS KEMAMPUAN MENULIS PUISI OLEH SISWA KELAS VIII SMP NEGERI 2 KOTA PONTIANAK - Anastasia; Yuliansyah, Aqis; Hajjafiani, Dini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The general objective of this study is "To find out how the poetry writing ability of eighth grade students of SMP Negeri 2 Pontianak City". The specific objective of this study is to describe the poetry writing ability of eighth grade students of SMP Negeri 2 Pontianak City and to describe the factors that influence the poetry writing ability of eighth grade students of SMP Negeri 2 Pontianak City. The type of research used is descriptive research in the form of a case study approach. By using interactive model analysis techniques according to Mines & Huberman The results of the study found that the poetry writing ability of eighth grade students of SMP Negeri 2 Pontianak City has not reached the expected level and still requires significant improvement to reach the category of being able to write poetry so that efforts are needed to improve students' poetry writing ability through developing imagination and using creative language styles.